Framing Toleransi Beragama Pada Era Post Truth: Telaah Situs Online Alif.id - Setiawan, Muhamad Agung (Fakultas Ushuluddin, Adab, dan Dakwah IAIN Parepare, 2023)
This research aims to determine the framing of religious tolerance on the internet on the online site alif.id. The objects of this research are three articles on the online site alif.id, which discuss religious tolerance. The research method used is qualitative research using Zhongdan Pan and Gerald M. Kosicki's framing analysis model, which focuses on syntactic, script, thematic, and rhetorical elements to identify an article in the discourse on religious tolerance on the online site alif.id. The results of this research show that on the online site alif.id there are three articles discussing religious tolerance: Chinese Muslims and Tolerance in Semarang, Learning Tolerance from the Village, and Examples of Tolerance from Companions of the Prophet. Regarding syntactic structure, the three articles framing religious tolerance use a historical and social approach. Meanwhile, in terms of script, each article puts forward various practices of religious tolerance by looking at it from the 5W+1H angle. Meanwhile, in the thematic structure, each article raises a different theme, namely around the issue of racism among ethnic Chinese Muslims in Semarang, through an ethnographic approach to the values of tolerance that exist in Kaloran and discussing the role model of tolerance practised by Khulafa' Rasyidin. As seen from the rhetorical element, the three articles emphasise the importance of tolerance through various sentences accompanied by explanations that strengthen the practice of religious tolerance.